Assessing People’s Values of Nature: Where Is the Link to Sustainability Transformations? - Stålhammar, Sanna (Frontiers in Ecology and Evolution, 2021)
The efforts to measure people’s current preferences and values of ecosystem services raise questions about the link to sustainability transformations. The importance of taking social and cultural values of nature into account is increasingly recognised within ecosystem services research and policy. This notion is informing the development and application of social (or socio-cultural) valuation methods that seek to assess and capture non-material social and cultural aspects of benefits of ecosystems in non-monetary terms. Here, ‘values’ refer to the products of descriptive scientific assessments of the links between human well-being and ecosystems. This precise use of the values term can be contrasted with normative modes of understanding values, as underlying beliefs and moral principles about what is good and right, which also influence science and institutions. While both perspectives on values are important for the biodiversity and ecosystem services agenda, values within this space have mainly been understood in relation to assessments and descriptive modes of values. Failing to acknowledge the distinction between descriptive and normative modes bypasses the potential mismatch between people’s current values and sustainability transformations. Refining methodologies to more accurately describe social values risks simply giving us a more detailed account of what we already know—people in general do not value nature enough. A central task for values studies is to explore why or how peoples’ mindsets might converge with sustainability goals, using methods that go beyond assessing current states to incorporate change and transformation.